THE CORPORATE ADVANTAGE OF LEVERAGING DETERMINANTS IN THE VOLUNTARY CARBON OFFSET IN INDONESIA'S NEW CAPITAL CITY - Adinda Dyah Pitaloka; Poppy Alvianolita Sanistasya (RADJA PUBLIKA, 2025)
The purpose of this study is to analyze and explain the implementation of the carbon offset program contributing to sustained competitive advantage for Telkomsel. The type of research used is descriptive research with a qualitative approach. The large number of people who are not yet aware of the importance of carbon offset is one of the major challenges, even though contributions to this initiative can provide a sustainable competitive advantage for the company, by improving its reputation, attracting environmentally conscious consumers, and meeting increasingly stringent regulatory demands. The carbon offset program can provide a sustainable competitive advantage for Telkomsel by improving the company's image, attracting customers and investors, and utilizing government incentives. The limitation of the study is that many people are not yet aware of this program.